(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research paper studies the asymmetry in knee extensor strength of dominant leg betweenInteruniversity and College Handball Players. Utilizing the CSMI HUMAC NORM Isokinetic Dynamometer,measured knee extensor strength in Newton meters (Nm) in both groups, comprising 30 subjects (15 ineach group) from LNIPE, NERC, Guwahati, Assam. The study aimed to determine if there were significantdifferences in knee extensor strength of dominant leg of the handball players asymmetry between thesetwo categories of handball players. The statistical analysis employed a t-test to compare the means ofthe two groups.